Atheroprotective Flow Upregulates ITPR3 (Inositol 1, 4, 5-Trisphosphate Receptor 3) in Vascular Endothelium via KLF4 (Krüppel-Like Factor 4)-Mediated Histone Modifications. Issue 5 (May 2019) - He, Ming; Huang, Tse-Shun; Li, Shuai; Hong, Hsiao-Chin; Chen, Zhen; Martin, Marcy; Zhou, Xin; Huang, Hsi-Yuan; Su, Shu-Han; Zhang, Jiao; Wang, Wei-Ting; Kang, Jian; et al.
Abstract : Objective—: The topographical distribution of atherosclerosis in vasculature underscores the importance of shear stress in regulating endothelium. With a systems approach integrating sequencing data, the current study aims to explore the link between shear stress-regulated master transcription factor and its regulation of endothelial cell (EC) function via epigenetic modifications. Approach and Results—: H3K27ac (acetylation of histone 3 lysine 27)-ChIP-seq (chromatin immunoprecipitation followed by high throughput sequencing), ATAC-seq (an assay for transposase-accessible chromatin-sequencing), and RNA-seq (RNA-sequencing) were performed to investigate the genome-wide epigenetic regulations in ECs in response to atheroprotective pulsatile shear stress (PS). In silico prediction revealed that KLF4 binding motifs were enriched in the PS-enhanced H3K27ac regions. By integrating PS- and KLF4-modulated H3K27ac, we identified 18 novel PS-upregulated genes. The promoter regions of these genes showed an overlap between the KLF4-enhanced assay for transposase-accessible chromatin signals and the PS-induced H3K27ac peaks. Experiments using ECs isolated from mouse aorta, lung ECs from EC-KLF4-TG versus EC-KLF4-KO mice, and atorvastatin-treated ECs showed that ITPR3 (inositol 1, 4, 5-trisphosphate receptor 3) was robustly activated by KLF4 and statins. KLF4 ATAC-qPCR (quantitative polymerase chain reaction) and ChIP-qPCR further demonstrated that a specific locus in the promoter region of the ITPR3 gene was essential for KLF4 binding, H3K27ac enrichment, chromatin accessibility, RNA polymerase II recruitment, and ITPR3 transcriptional activation. Deletion of this KLF4 binding locus in ECs by using CRISPR-Cas9 resulted in blunted calcium influx, reduced expression of endothelial nitric oxide synthase, and diminished nitric oxide bioavailability. Conclusions—: These results from a novel multiomics study suggest that KLF4 is crucial for PS-modulated H3K27ac that allow the transcriptional activation of ITPR3. This novel mechanism contributes to the Ca 2+ -dependent eNOS (endothelial nitric oxide synthase) activation and EC homeostasis. Abstract : Supplemental Digital Content is available in the text.